Transformed Into Digital Resources - a New Life for the Cultural Heritage Related Research and Scientific Archives - Radovesta Stewart; Stanislav Simeonov (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2019)
For decades, museum specialists have kept their research on paper precious invaluable work. Today, this lost knowledge can be made available again. By digitalizing these studies and providing them with open access will offer scope for a deeper study of the Bulgarian cultural heritage, an integral part of which are the works of the investigators, ethnographers, historians, archaeologists. The paper gives a further look into the process of digitalizing old studies related to the cultural heritage initially from the archives of Regional historical museum Burgas. The described model is universal and can be a base for other cultural organizations that would like the ability to open their archives up to third parties, make them easy accessible, easy to maintain and become more sustainable.